Improving surface hardness of AISI 1045 steels using melamine derived from urea - Elias Tadesse Fisha (Heat Treatment and Surface Engineering, 2024)
AISI 1045 steels are medium carbon steels used in applications that require greater strength and hardness such as gears, railway wheels and tracks, crankshafts, rolls, axles and other structural components. Although AISI 1045 steels are highly demanded engineering materials, they suffer from deformation and wear resistance when these applications are used. The hardness and wear resistance of the material are improved using a surface hardening method. Pack nitriding is the cheapest and easiest method of surface hardening method implemented in this work. The surface hardness of AISI 1045 steel is improved by the diffusion of nitrogen from the nitrogen-bearing material (melamine) to the surface of the steel and forms a metal nitride compound, which has strong hardness and wear resistance. This work reports that substantial surface hardening of AISI 1045 steel was achieved by the pack nitriding method using melamine obtained by in situ reaction of urea. The surface hardness increases manifold with the amount of melamine used, soaking time and temperature. The microscopic investigations of the nitrided surfaces of the metal show the formation of two distinct layers. The microstructural properties and hardness of the samples before and after nitriding were thoroughly investigated and interpreted.